EU Enlargement, Migration, and Lessons from German Unification - Hans-Werner Sinn (Center for Economic Studies and ifo Institute (CESifo), 1999)
The paper studies the role of international implications after EU enlargement. Based on a formal model with migration costs for both capital and labor, it predicts a two-sided migration from the new to the old EU countries which is later reversed. As the migration pattern chosen by market forces turns out to be effici e nt, migration should not be artificially reduced by means of legal constraints or subsidies to the new member countries. The paper draws the parallel with German unification and points out the lessons to be learned by Europe. The analysis concludes with a brief discussion of the second best problem posed by the existence of welfare states in the old member countries.
Keywords: 330; EU enlargement; migration; welfare state